Editorial - Oniwide, Oyetola (NIU Journal of Educational Research, 2025)
This edition of NIU Journal of Educational Research touches on Cloud Computing Technology for Library Services, School-Health Modifier Management Package, Staff Development in Business Education, Impact and Challenges of Homeschooling on the Socialization of Primary School-Aged Children, Digital Tools on Traditional Graphic Design Techniques in Some Tertiary Institutions, Muscic Education and Entrepreneurship Education. One of the papers, in this issue, reveals that while librarians recognize the potential of cloud computing to enhance service delivery, improve access to digital resources, and support teaching and research, there are significant gaps in awareness and practical adoption. The paper therefore, highlights the need for targeted educational initiatives, increased funding, and regular training to equip librarians with the skills required to leverage new technologies effectively. It is, therefore, suggested that a need for strategic shift from traditional to personalized, technology-driven services is essential, with cloud computing serving as a catalyst for improved efficiency and broader access to information resources. Another paper also reveals that while homeschooling offers a range of educational benefits such as the ability to tailor the curriculum to meet the needs of the child and the potential for one-on-one attention, it has unique challenges for the social skills development of primary school children which include limited peer interaction, parental oversight and involvement, sociocultural factors among others. The paper therefore, recommends strategies to enhance socialization in homeschooling such as promoting structured social opportunities, fostering peer interaction through technology, developing mentor relationships, encouraging extracurricular engagement amongst others. On the whole, this issue of NIU Journal of Educational Research features many empirical and theoretical based articles which can be of great benefit to every reader.